2023
DOI: 10.7759/cureus.40333
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Low-Dose Versus High-Dose Parenteral Ketorolac for Acute Pain Relief in Patients 65 Years and Older in the Emergency Department

Abstract: Background There is limited data surrounding acute pain management in elderly ED patients. Ketorolac is a potent non-steroidal anti-inflammatory drug (NSAID) with dose/duration-dependent side effects. There is evidence that an analgesic ceiling effect exists for parenteral ketorolac doses greater than 10 milligrams (mg); however, this has not been studied in patients 65 years and older. Methods This was a retrospective chart review of ED patients 65 years and older who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…[1][2][3] Despite their benefits, caution should be exercised, particularly in geriatric patients, due to potential side effects. [4][5][6] Among the NSAIDs used during the perioperative period after TKA, ketorolac is commonly administered. This drug has shown efficacy in providing analgesia; however, evidence suggests a ceiling effect for its potency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Despite their benefits, caution should be exercised, particularly in geriatric patients, due to potential side effects. [4][5][6] Among the NSAIDs used during the perioperative period after TKA, ketorolac is commonly administered. This drug has shown efficacy in providing analgesia; however, evidence suggests a ceiling effect for its potency.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, ketorolac is associated with adverse gastrointestinal, renal, and cardiovascular events, some of which may be dose-dependent or duration-dependent. 5 Studies on low-dose ketorolac have demonstrated effective analgesia after spinal fusion surgery compared with a placebo. 9,10 However, limited evidence exists regarding its use in TKA, with a study by Zhou et al reporting no significant difference in pain relief after a single dose of ketorolac (15 mg or 30 mg) compared with placebo following TKA.…”
Section: Introductionmentioning
confidence: 99%